When does spiritual intelligence particularly predict job engagement? The mediating role of psychological empowerment - Mohsen Torabi; Iman Zohoorian Nadali (Wolters Kluwer Medknow Publications, 2016)
Background: Regarding the importance of health care providers such as nurses who are always in stressful environments, it is imperative to better understand how they become more engaged in their work. The purpose of this paper is to focus on health care providers (nurses), and examine how the interaction between spiritual intelligence and psychological empowerment affect job engagement. Materials and Methods: This descriptive and quantitative study was conducted among nurses at the Faghihi Hospital in Shiraz, Iran in 2010. A sample of nurses (n = 179) completed standard survey questionnaire including spiritual intelligence, psychological empowerment, and job engagement which included 5 questions for each dimensions. For testing the hypotheses of the study, results were analyzed through structural equation modeling (SEM) using LISREL 8.8. Results: SEM revealed that psychological empowerment could fully mediate the relationship between spiritual intelligence and job engagement. However, the correlation between spiritual intelligence and job engagement was significant but weak using Pearson coefficient method. This can imply that psychological empowerment plays a crucial role in the relationship between spiritual intelligence and job engagement. Conclusions: This paper indicates that spiritual intelligence might affect different organizational parameters, directly or indirectly. Therefore, it is recommended that the researchers evaluate probable relationships between spiritual intelligence and other variables.